2013
DOI: 10.1111/jcpe.12040
|View full text |Cite
|
Sign up to set email alerts
|

Full‐mouth disinfection as a therapeutic protocol for type‐2 diabetic subjects with chronic periodontitis: Twelve‐month clinical outcomes. A randomized controlled clinical trial

Abstract: The treatments did not differ with respect to clinical parameters, including the primary outcome variable (i.e. changes in clinical attachment level in deep pockets), for up to 12 months post-treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 31 publications
1
52
0
3
Order By: Relevance
“…In the da Cruz et al 30 study, patients with well‐controlled and poorly controlled DM were pooled, and the mean 9.23% ± 2.60% of HbA1c levels at baseline showed a slight increase to 9.4% ± 2.53% 3 months after full‐mouth SRP. A randomized controlled clinical trial 36 that used chlorhexidine in a full‐mouth disinfection protocol in patients with poorly controlled DM (HbA1c 10.0% ± 2.4% at baseline) did not find significant improvement of glycemic levels for up to 12 months post‐treatment. Thus, in several studies, the results of the effects of periodontal treatment on HbA1c levels appear to be independent of the pretreatment level of glycemic control.…”
Section: Discussionmentioning
confidence: 97%
“…In the da Cruz et al 30 study, patients with well‐controlled and poorly controlled DM were pooled, and the mean 9.23% ± 2.60% of HbA1c levels at baseline showed a slight increase to 9.4% ± 2.53% 3 months after full‐mouth SRP. A randomized controlled clinical trial 36 that used chlorhexidine in a full‐mouth disinfection protocol in patients with poorly controlled DM (HbA1c 10.0% ± 2.4% at baseline) did not find significant improvement of glycemic levels for up to 12 months post‐treatment. Thus, in several studies, the results of the effects of periodontal treatment on HbA1c levels appear to be independent of the pretreatment level of glycemic control.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, a randomized clinical trial comparing FDM with and without CHX showed no differences in the periodontal clinical parameters PD and CAL at 3, 6, and 12 months after treatment 43 . In addition, a recent systematic review and meta‐analysis designed to evaluate the clinical effect of FMD compared with QS showed no benefit of FMD over QS for changes in PD and gain in CAL.…”
Section: Discussionmentioning
confidence: 97%
“…, Santos et al. ). Doxycycline at antimicrobial and sub‐antimicrobial doses has been long the most evaluated medication as adjunct to SRP for treatment of diabetic subjects (Grossi et al.…”
mentioning
confidence: 99%